2012
DOI: 10.1002/art.34568
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: To squeeze or not to squeeze, that is the question! Optimizing the Disease Activity Score in 28 joints by adding the squeeze test of metatarsophalangeal joints in early rheumatoid arthritis

Abstract: Objective. To optimize use of the Disease Activity Score in 28 joints (DAS28) in early rheumatoid arthritis (RA) by adding the "squeeze test" of forefeet.Methods. The squeeze test is used to examine bilateral compression pain (BCP) across the metatarsophalangeal (MTP) joints. For this study, data for patients participating in the Treatment in the Rotterdam Early Arthritis Cohort study, an ongoing clinical trial that evaluates different induction therapies in patients with early RA, were randomly divided into 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Interestingly, this does not include the foot in its assessment. De Jong et al performed a study where they added a squeeze test across the MTPJs in their assessment using the DAS 28 [13]. They found that this had greater sensitivity for the assessment of disease severity in patients presenting with early RA.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Interestingly, this does not include the foot in its assessment. De Jong et al performed a study where they added a squeeze test across the MTPJs in their assessment using the DAS 28 [13]. They found that this had greater sensitivity for the assessment of disease severity in patients presenting with early RA.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Recently, rheumatologists adopted the "treat to target" therapeutical protocol for treating early RA. [1][2][3][4] The main strategy of the therapy is assessing disease activity on a regular basis to achieve a certain target. In daily practice disease activity assessment is usually done with Disease Activity Score 28 (DAS28) because it is clinically applicable.…”
Section: Introductionmentioning
confidence: 99%
“…In daily practice disease activity assessment is usually done with Disease Activity Score 28 (DAS28) because it is clinically applicable. [1][2][3] DAS28 has been developed and validated using data from clinical research. Unfortunately, a valid instrument developed from a set of clinical research data is not neccesary became a valid instrument in daily practice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations